Utilize Extreme Programming Method for Developing Financial Report Standards Apps - Al Amin, Budi; Sutanto, Yusuf; Susanti, Nani Irma (Journal of Information System and Informatics, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in providing employment opportunities, especially when job competition in the formal sector is intense. Eliza Catering, an MSME located in Surakarta city, operates in the culinary sector and traditionally maintains simple financial records. This practice hampers the ability to accurately measure the company's performance and determine its profitability. This research aims to document the daily transactions of Eliza Catering using the BukuKas application and to generate financial reports in accordance with Financial Accounting Standards (FAS) EMKM. The data analysis process involved three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that Eliza Catering previously only recorded income, lacking comprehensive financial documentation. By utilizing the BukuKas application, daily transactions were systematically recorded. The Extreme Programming method was employed to develop this research system, resulting in the preparation of financial reports based on FAS EMKM, which include profit and loss statements, financial position reports, and notes to the financial statements.